Response of Media to the War: the Case of Ukraine’s United News Telethon - Nataliia Karpchuk; Serhii Fedoniuk (Codrul Cosminului)
In the conditions of war, the conflicting parties use the available means of communica-tion to interact with the public and to achieve their strategic goals. The rapid develop-ment of communication technologies provides new communication opportunities. Even though the current war of the Russian Federation against Ukraine is called “The First Social Media War”, a powerful information role was played by television, particularly the United News telethon, founded by the largest media groups of Ukraine in the first days of the war. Media channels stopped their separate broadcasting and divided a common telecast among them to inform 24/7. The article analyses the achievements of this new practice of news reporting, particularly the consolidation of society, the influ-ence on public opinion and support for government decisions, the provision of objective and verified information, the fight against fakes, the ability of channels to survive in wartime, etc. However, the unification of the news presentation format is criticised due to the uniformity of the content, the lack of alternative points of view, and the domi-nance of the authorities in the media space. The possible transfor-mation/disappearance of the United News telethon is outlined.